Elegies for understanding the psychological state of poets -example of Şeref Hanim - Nazik, Sitki (Gazi Universitesi, Turk Kulturu ve Haci Bektas Veli, 2016)
Elegies are a poetry genre of classical Turkish literature and they are filled with emotion and sung over dead people. It is, even a little, possible to understand the poet's psychological state from those poems in which lyricism is highly felt. The subject of this study is to analyze the psychological state of the poet in the context of elegies. However, the scope of the study is limited to the elegies in şeref Hanim Divan. Because, it is easier to detect the psychological state of şeref Hanim, as she is a lady, who became famous in elegy genre. The purpose of the study is to ensure that both the poet's psychology and the psychological aspect of classical poetry are recognized more closely together with the aforementioned genre. The poems selected among the elegies of şeref Hanim Divan have been rendered in this study by considering the subject integrity. The poems that were analyzed in this study are the ones that carry şeref Hanim's intensive emotions and feelings. Rather than transmitting the sample poems with direct sentences through present Turkish language, the study is focused on their meanings, in one respect; meaning-based annotation method is applied in this study. As the elegy is genre of poems expressing sadness and pain for the death of a loved one, grudge and anger developed against the ones causing death, if there is any, the elegy has enabled us to recognize only the sadness and hatred aspects of the poet's psychology.
Şairin psikolojik yönünü anlamaya yardimci olmasi bakimindan mersiyeler -şeref hanim örne?i
Keywords: Classical Turkish poetry; Divan; Elegy; Psychology; Şeref Hanim